KESALAHAN TATA BAHASA PADA SURAT IZIN DI SEKOLAH YANG DITULIS OLEH SISWA KELAS VIII SMP NEGERI 1 AMANDRAYA TAHUN PEMBELAJARAN 2021/2022 - Fedirman Laia (Kohesi : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
It is stated that one of the materials studied in the subjects Indonesian in class VII is to write a license at the School. The use of spelling in the form (writing letters, words and absorption elements), and punctuation marks (dots, colons, commas, and slashes) is still minimal so that the results of writing are poorly understood. The purpose of this study is to describe the error of writing letters, writing words, on permits in schools, written by students of grades VIII-1 of State Junior High School 1 Amandraya and Describes the error of the punctuation point, comma, on the license at school. The research method used is a qualitative research method with documentation techniques. Data analysis techniques in this study are data reduction, data presentation, and conclusions. The results showed some mistakes made by students of class VIII-1 of SMP Negeri 1 Amandraya with a total of 23 students, there were 3 people who had never been alpa and 20 people had been alpa. From 20 student letters, there were 72 errors. The most grammatical usage errors are letter writing there are thirty-seven errors, letter writing there are twenty-five errors, the use of points there are five errors, and the use of commas there are five errors. Based on the results of the study, it can be concluded that the permit written by students of class VIII-1 of SMP Negeri 1 Amandraya, there were 72 errors from 20 pieces of student permits. The dominant mistake is the use of spelling in letter writing there are 37 and word writing as many as 25 errors, and the non-dominant error is the use of point and comma punctuation marks, each of which has 5 errors. In addition, almost all students have not been able to write letters according to their structure. In this study, researchers suggest: Students can understand the use of good and correct grammar and continue to practice in writing letters by paying attention to spelling and punctuation elements and continue to learn to multiply vocabulary so as to facilitate the language spoken clearly.